Follow the money the Audit Commission, public money and the management of public services, 1983-2008 - Campbell-Smith, Duncan (Allen Lane, 2008)
Published to coincide with the Audit Commission's 25th anniversary, 'Follow the Money' is a narrative history tracing how the Commission acquired, sustained and exerted influence on government and public spending in the years between Margaret Thatcher's rise to power and the departure of Tony Blair.